Data-Driven Futures: The Role of Analytics in the Olympic Rise of eSports - Diaz, Cesar; Florez, Hector (Revista Científica, 2024)
The International Olympic Committee (IOC) hosted the first Olympic Virtual Series in 2021, including eCycling, eBaseball, and League of Legends, among others. Later, in 2023, the first Olympic eSports Series was held in Singapore and organized by the IOC. This shows that the recent recognition of eSports on the Olympic stage is more than a gesture of inclu-sion; it is a powerful acknowledgment that digital competition has matured into a discipline where reflex, cognition, and strategy demand the same respect as endurance and physical strength. Yet this recognition also invites a deeper question: how do we train and protect athletes in a domain where the battleground is not the field but the interface? The answer lies increasingly in data.